Modulation of both activator protein-1 and nuclear factor-kappa B signal transduction of human T cells by amiodarone. (January 2015) - Cheng, Shu-Meng; Lin, Wei-Hsiang; Lin, Chin-Sheng; Ho, Ling-Jun; Tsai, Tsung-Neng; Wu, Chun-Hsien; Lai, Jenn-Haung; Yang, Shih-Ping
Amiodarone, a common and effective antiarrhythmic drug, has been reported to have anti-inflammatory effects such as reducing the activation and movement of neutrophils. However, its effects on human T cells remain unclear. The aim of this study was to elucidate the effects and possible underlying mechanisms of amiodarone on human T cells. We isolated human primary T cells from the peripheral blood of healthy volunteers and performed enzyme-linked immunosorbent assay (ELISA), flow cytometry, electrophoretic mobility shift assay, luciferase assay, and Western blotting to evaluate the modulatory effects of amiodarone on human T cells. We found that amiodarone dose dependently inhibited the production of cytokines, including interleukin-2 (IL-2), IL-4, tumor necrosis factor-alpha, and interferon-gamma in activated human T cells. By flow cytometry, we demonstrated that amiodarone suppressed the expression of IL-2 receptor-alpha (CD25) and CD69, the cell surface markers of activated T cells. Moreover, molecular investigations revealed that amiodarone down-regulated activator protein-1 (AP-1) and nuclear factor kappa-B (NF-κB) DNA-binding activities in activated human T cells and also inhibited DNA binding and transcriptional activities of both AP-1 and NF-κB in Jurkat cells. Finally, by Western blotting, we showed that amiodarone reduced the activation of c-Jun NH2 -terminal protein kinase and P38 mitogen-activated protein kinase, and suppressed stimuli-induced I-kappa B-alpha degradation in activated human T cells. Through regulation of AP-1 and NF-κB signaling, amiodarone inhibits cytokine production and T cell activation. These results show the pleiotropic effects of amiodarone on human T cells and suggest its therapeutic potential in inflammation-related cardiovascular disorders.